2022
DOI: 10.3390/en15145198
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Delivery Time within the Distribution Network, Taking into Account Fuel Consumption and the Level of Carbon Dioxide Emissions into the Atmosphere

Abstract: The evolution of changes in shopping in the modern society necessitates suppliers to seek new solutions consisting of increasing the efficiency of transport processes. When it comes to controlling the flow of goods in modern distribution networks, planning and timely deliveries are of particular importance. The first factor creating a competitive advantage involves the tendency to shorten order delivery times, especially for products with a short shelf life. Shorter delivery times, in turn, extend the period o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…The constructed surrogate models should have well-formed characteristics such as polynomial functions, radial basis functions (RBF), Kriging models, and support vector regressions [41]. Surrogate optimization has received significant research consideration for various applications, such as desalination microgrids [42], multi-generation energy system [43], resource allocation and network routing [44], electromagnetic [45], infrastructure of electric bus charging [46], and distribution network delivery time [47]. A fractional PID controller is challenging compared to a classical PID controller.…”
Section: Optimization Techniquesmentioning
confidence: 99%
“…The constructed surrogate models should have well-formed characteristics such as polynomial functions, radial basis functions (RBF), Kriging models, and support vector regressions [41]. Surrogate optimization has received significant research consideration for various applications, such as desalination microgrids [42], multi-generation energy system [43], resource allocation and network routing [44], electromagnetic [45], infrastructure of electric bus charging [46], and distribution network delivery time [47]. A fractional PID controller is challenging compared to a classical PID controller.…”
Section: Optimization Techniquesmentioning
confidence: 99%
“…Optimization of a single criterion transport process based on the time or cost criterion often leads to a reduction in adverse impacts on the environment [37][38][39]. The publication [40], based on the example of a perishable product distribution network, demonstrated that achieving an optimal solution for the transport time criterion could lead to a reduction in fuel consumption and CO 2 emissions into the atmosphere, while the authors of [41], using an example of supply chains in France, demonstrated a strong correlation between logistics costs and CO 2 emissions using only road transport.…”
Section: Literature Reviewmentioning
confidence: 99%
“…When trucks and passenger vehicles are mixed in using a freeway service, the state of trafc fow changes signifcantly, and associated negative impact occurs in terms of efciency and safety concerns, especially at freeway entrance and exit ramps. As trucks reduce the overall trafc efciency, mixed trafc may incur trafc congestion, increase the emissions of pollutants, and pose potential safety risks (e.g., [2][3][4][5][6][7][8]). To deal with these negative issues, several truck restriction strategies have been proposed to reduce the adverse impact caused by trucks.…”
Section: Introductionmentioning
confidence: 99%